PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN ANAK MELALUI PENGGUNAAN MEDIA KARTU KATA DI TK KARTIKA XX-5 KOTA MAKASSAR - Nasaruddin R; A. Rezky Nurhidaya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2018)
Abstract: Improving the Reading Ability of the Beginning of Children Through the Use of Word Card Media in Kartika XX-5 Kindergarten Makassar City. This study aims to determine the improvement of children's early reading skills through the use of word card media in the Kartika XX-5 Kindergarten of Makassar City. This study provides information on the ability of early reading through the use of word cards in children in kindergarten. The type of research used is using Classroom Action Research. The location of this study was TK Kartika XX-5 in Makassar City with the subject being group B children with 15 students. The instruments used in this study were observation / documentation and documentation. The results of this study indicate that the use of word cards can improve initial reading. The use of word card media in the learning process can help children improve their initial reading skills. Increasing these abilities in terms of students are able to recognize letters / words, connect images with letter symbols / words, and are able to call the symbols of vowels and consonants that are known around the environment.